Genres : lettre d'information du Centre Lesbien, Gai, Bi & Trans de Paris. (Paris : Centre Lesbien, Gai, Bi & Trans de Paris, 2007)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 3 rue Keller, 75524 Paris cédex 11
Frans
Periodiek